2020
DOI: 10.26838/medrech.2020.7.6.462
|View full text |Cite
|
Sign up to set email alerts
|

AN Unusual case of osteoblastoma in an elderly female: A case report and a review

Abstract: Osteoblastoma is a rare entity encountered as a benign osseous tumor with the propensity of occurrence towards the vertebral column and long bones. Commonly occurs in young middle-aged males with mandible as a site of predilection in the facial skeleton. Differential diagnosis of osteoblastoma holds a challenge in attaining a final diagnosis. Osteoid osteoma, cementoblastoma, osteosarcoma, aggressive fibrous dysplasia, and ossifying fibroma share a similar clinical behavior, radiological and histological behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…A few publications in the literature correlated the log reduction in MRD assessment with survival where researchers studied MRD level as a continuous variable determined by flow cytometry and demonstrated survival benefits in MM patients per log depletion in MRD. 54 55 Likewise, our group also demonstrated that gradual fall in MRD levels from 0.1 to 0.001% is predictive of superior survival outcomes 35 ( Fig. 4 ).…”
Section: Caveats and Pitfalls Of Flow-based Mrd Assessment In MMmentioning
confidence: 53%
See 3 more Smart Citations
“…A few publications in the literature correlated the log reduction in MRD assessment with survival where researchers studied MRD level as a continuous variable determined by flow cytometry and demonstrated survival benefits in MM patients per log depletion in MRD. 54 55 Likewise, our group also demonstrated that gradual fall in MRD levels from 0.1 to 0.001% is predictive of superior survival outcomes 35 ( Fig. 4 ).…”
Section: Caveats and Pitfalls Of Flow-based Mrd Assessment In MMmentioning
confidence: 53%
“…Thus, using clonal PC as numerator and total PC as denominator, we defined NPCI, as NPCI = clonal PC/total PC. 35…”
Section: Analytical Considerations For Mfc-based Mrd Detectionmentioning
confidence: 99%
See 2 more Smart Citations